Neurodevelopmental disorders. (April 2017) - Thapar, Anita; Cooper, Miriam; Rutter, Michael
Summary: Neurodevelopmental disorders such as attention deficit hyperactivity disorder (ADHD) and autism spectrum disorder, although most commonly considered in childhood, can be lifelong conditions. In this Personal View that is shaped by clinical experience and research, we adopt a conceptual approach. First, we discuss what disorders are neurodevelopmental and why such a grouping is useful. We conclude that both distinction and grouping are helpful and that it is important to take into account the strong overlap across neurodevelopmental disorders. Then we highlight some challenges in bridging research and clinical practice. We discuss the complexity of clinical phenotypes and the importance of the social context. We also argue the importance of viewing neurodevelopmental disorders as traits but highlight that this is not the only approach to use. Finally, we consider developmental change across the life-span. Overall, we argue strongly for a flexible approach in clinical practice that takes into consideration the high level of heterogeneity and overlap in neurodevelopmental disorders and for research to link more closely to what is observed in real-life practice.